The role of the bureau of government and regional autonomy in facilitating regional government cooperation with third parties in West Sumatra Province - Febrian Muharromah; Rizki Syafril (Privietlab, 2026)
Regional autonomy provides regional governments with the authority to manage governmental affairs and public interests based on the needs and potential of each region. In its implementation, regional governments are required to improve the quality of public services, strengthen regional development, and create effective and efficient governance systems. However, the limitations of financial resources, human resources, and technology often become obstacles in the implementation of regional development. Therefore, cooperation between regional governments and third parties is an important strategy for supporting development programs and improving public services. This study aims to analyze the role of the Bureau of Government and Regional Autonomy in facilitating cooperation between regional governments and third parties in West Sumatra Province. This research uses a qualitative literature study (library research) approach, analyzing laws and regulations, official government documents, and previous scholarly studies on coordination, communication, administrative management, and monitoring and evaluation in regional cooperation activities. The results indicate that the Bureau of Government and Regional Autonomy plays a strategic role as a facilitator, coordinator, and administrator in implementing regional cooperation. The challenges identified include delays in document submission, differences in understanding among institutions, and limited use of information technology. Improvements in coordination systems, administrative management, and information technology are necessary to support optimal regional cooperation.